Jay Pather, performance, and spatial politics in South Africa - Katrak, Ketu H. (African expressive cultures., 2021)
"Jay Pather, Performance and Spatial Politics in South Africa offers the first full-length monograph on the award-winning choreographer, theater director, curator, and creative artist in contemporary global performance. Working within the contexts of African studies, dance, theater, and performance, Ketu H. Katrak explores the extent of Pather's productive career but also places him and his work in the South African and global arts scene, where he is considered a visionary. Pather, a South African of Indian heritage, is known as a master of space, site, and location. Katrak examines how Pather's performance practices place him in the center of global trends that are interdisciplinary, multidisciplinary, collaborative, and multimedia and that cross borders between dance, theater, visual art, and technology. Jay Pather, Performance and Spatial Politics in South Africa offers a vision of an artist who is strategically aware of the spatiality of human life, who understands the human body as the nation's collective history, and who is a symbol of hope and resilience after the trauma of violent segregation"--